The Genetics of PTPN1 and Obesity: Insights from Mouse Models of Tissue-Specific PTP1B Deficiency - Ryan C. Tsou; Kendra K. Bence (Hindawi Limited, 2012)
The protein tyrosine phosphatase PTP1B is a negative regulator of both insulin and leptin signaling and is involved in the control of glucose homeostasis and energy expenditure. Due to its prominent role in regulating metabolism, PTP1B is a promising therapeutic target for the treatment of human obesity and type 2 diabetes. The PTP1B protein is encoded by the PTPN1 gene on human chromosome 20q13, a region that shows linkage with insulin resistance, type 2 diabetes, and obesity in human populations. In this paper, we summarize the genetics of the PTPN1 locus and associations with metabolic disease. In addition, we discuss the tissue-specific functions of PTP1B as gleaned from genetic mouse models.